Using abundance indices and fishing effort data to tune catch-at-age analyses of sprat Sprattus sprattus L., whiting Merlangius merlangus L. and spiny dogfish Squalus acanthias L. in the Black Sea - Daskalov G. (Dynamique des populations marines, 1998)
Stock assessments based on both fisheries data and abundance indices have been carried out on three fishery ecosystem species important for the Black Sea: the sprat, the whiting and the spiny dogfish. Two methods of catch-at-age analysis (CAA) have been applied: the virtual populations analysis (VPA) with ad hoc tuning and the extended survivors analysis (XSA). Their relevance to the data on the three stocks has been investigated. The consistency of alternative assessment options has been explored using retrospective analyses. The final assessment results have been discussed in the light of interactions among the three species and the global situation of the Black Sea ecosystem.
Deuxième Réunion du Groupe de Travail DYNPOP, 1996/10/02-05, Genova (Italy)